A LITERATURE REVIEW ON NETWORK SIMULATION APPLICATION DEVELOPMENT USING VISUAL PROGRAMMING LANGUAGES - Wicaksono, Yosep Aditya; Archaqie, Haikal Nur Rachmanrachim (UNIVERSITAS STEKOM, 2025)
This study investigates the development of network simulation applications using visual programming languages, aiming to map current trends, tool preferences, and key implementation challenges in educational and experimental contexts. Through a structured literature review of 28 academic sources, the research identifies the increasing adoption of visual-based interfaces, such as VB.NET, C# WinForms, and tools like Cisco Packet Tracer, as essential platforms to support interactive learning in computer networking. Visual simulation environments are found to enhance conceptual understanding, reduce cognitive load, and improve student engagement, particularly among non-technical users. Despite these advantages, the study reveals several limitations inherent in visual simulation tools. These include lack of modularity, limited protocol validation, and constrained interoperability across different vendors and platforms. Moreover, most existing tools operate in standalone environments and have not yet adapted to cloud-based or scalable architecture. The findings suggest a pressing need for hybrid simulation models that combine the intuitive user experience of GUI-based applications with the technical depth and flexibility of CLI or open API backends. This research contributes a systematic synthesis of the strengths and gaps within the current ecosystem of visual network simulators. It provides practical recommendations for educators, developers, and researchers aiming to build more adaptive, extensible, and context-aware simulation environments that align with modern educational and technological needs.